2017
DOI: 10.3329/bjms.v16i3.32862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Secretome Mesenchymal Stem Cells On Expression Interleukin 10 And Interleukin 17 in Mice Lupus Model

Abstract: Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune inflammatory disease with extensive clinical features. The role of Interleukin 10 (IL-10) is to promote autoantibody production and autoreactive B cell proliferation. Interleukin 17 (IL-17) associated with pathogenesis of SLE and positively correlated with disease activity. Intraperitoneal pristane can induce lupus in mice. Mesenchymal stem cells secretome work in paracrine effects asantiinflammatory and immunomodulation agent by suppressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Previous studies have also shown that MSCs alleviate lupus-like diseases by reducing the number of CD19 + B cells [39]. The secretions of MSCs reduce serum IL-10 levels in lupus mice [40]. This study demonstrated that hUCMSCs inhibited B cells; hUCMSC-EVs had on effects on B cells, and hUCMSCs or hUCMSC-EVs had no signi cant regulatory effects on IL-10.…”
Section: These Factors May Contribute To the Differences In Results O...supporting
confidence: 49%
“…Previous studies have also shown that MSCs alleviate lupus-like diseases by reducing the number of CD19 + B cells [39]. The secretions of MSCs reduce serum IL-10 levels in lupus mice [40]. This study demonstrated that hUCMSCs inhibited B cells; hUCMSC-EVs had on effects on B cells, and hUCMSCs or hUCMSC-EVs had no signi cant regulatory effects on IL-10.…”
Section: These Factors May Contribute To the Differences In Results O...supporting
confidence: 49%
“…This suppressive effect was caused by improved function and activity of Treg cells and decreased Th17 cell levels (Figueora et al, 2014). With the decrease in IL-17 levels produced by Th17 cells, Treg activity, in regulating the appearance of antibodies to selfantigens would run better, so that theclinical improvement of LES occurred (Nurudhin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also shown that MSCs alleviate lupus-like diseases by reducing the number of CD19 + B cells 50 . The secretions of MSCs reduce serum IL-10 levels in lupus mice 51 . This study demonstrated that hUCMSCs inhibited B cells; hUCMSC-EVs had no effects on B cells, and hUCMSCs or hUCMSC-EVs had no significant regulatory effects on IL-10.…”
Section: Discussionmentioning
confidence: 98%